Relation between renal resistive index in children with nephrotic syndrome - Pranoy Dey; Hage Niku (Indian Journal of Child Health, 2021)
Context: Renal resistive index (RRI) is a non-invasive marker of several kidney diseases. It is an indicator of resistance to flow within the kidneys, which is a calculation of relationship between systolic and diastolic renal pressure changes. However, there is a limited knowledge in the use of RRI in the management and prognostication of Nephrotic syndrome. Aims: The aim of this study was to see the relation of RRI with Nephrotic syndrome. Materials and Methods: This hospital-based analytical study was conducted over a period of 1 year (June 2019–May 2020) in a tertiary care teaching institution. All the Nephrotic syndrome cases admitted in the pediatric ward were included in the study after taking consent from the parents/guardians. USG renal Doppler was done and blood and urine investigations were done. The RRI recorded from renal Doppler was compared with different categories of Nephrotic syndrome. Results: A total 63 children admitted with Nephrotic syndrome were included in the study. The mean RRI value was 0.66±0.14, 0.64±0.15 and 0.66±0.12 as well as 0.63±0.12, 0.67±0.16 and 0.71±0.13 on the right and left kidney, respectively, for each upper, middle, and lower pole interlobar renal arteries. Thus, the average RRI value of right kidney was 0.65±0.09 and left kidney was 0.67±0.09. Neither of the kidneys showed significant relationship between RRI of different poles. Conclusion: In our study, we could not find the USG Doppler useful to predict the disease outcome in children with Nephrotic syndrome.